Pengaruh Kebijakan Program Keluarga Harapan Terhadap Penanggulangan Kemiskinan Di Kecamatan Bajeng Kabupaten Gowa - Munawwarah Sahib (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Manado, 2021)
This study discusses the Family Hope Program and its impact on poverty reduction in Bajeng District, Gowa Regency. This research was conducted with the aim of knowing the implementation of the Family Hope Program in Bajeng District of Gowa Regency and to find out whether the Family Hope Program has an effect on Poverty Reduction in Bajeng District of Gowa Regency. The type of research used in this research is descriptive quantitative in order to reveal facts related to the Family Hope Program and its effect on poverty reduction in the Bajeng district. The population in this study were all participants of the Family Hope Program in Bajeng distric. To measure the opinion of respondents through a questionnaire regarding the events and symptoms they experienced, the researchers used ascale technique Likert. The results showed that the implementation of the Family Hope Program (PKH) in Bajeng distric of, Gowa regency went very well. This is indicated by the average score obtained from the question items of 224 or 82.6% which indicates that the Family Hope Program in its implementation occupies the very high/very good category. This study also shows that PKH has a positive and significant effect on poverty reduction, which is 38.4% while the rest is explained by other factors. The implications of this research are that it is hoped that with the Hope Family Program, poor families can increasingly realize the importance of education and health so that no more children drop out of school because their parents are unable to meet their school needs, and it is hoped that all elements related to the implementation of the Family Hope Program can carry out their duties properly and responsibly so that the objectives of the policy can be achieved and it is also hoped that there will be data collection for prospective PKH participants which is carried out according to procedures and by prioritizing the interests of the poor in order to create justice for all Indonesian people and the Family Hope Program can truly right on target.